1995
DOI: 10.1111/j.1398-9995.1995.tb02581.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergen cross‐reactivity between Pityrosporum orbiculare and Candida albicans

Abstract: Pityrosporum orbiculare and Candida albicans extracts were separated by SDS-PAGE, and IgE binding was detected by immunoblotting with 21 patient sera that were RAST positive to both yeasts. Cross-wise inhibition was performed of IgE binding of a serum pool containing IgE antibodies to both yeasts. The pool was mixed with serial dilutions of P. orbiculare or C. albicans extracts, and incubated with strips containing separated allergen. IgE binding was quantified by densitometric scanning and percent inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 31 publications
3
33
0
4
Order By: Relevance
“…To evaluate the antibody specificity, the serum pool obtained from patients with SLE who were positive for anti-ER␣ antibodies was diluted 1:100 in PBST and incubated overnight at room temperature in the presence of 40 g/ml of ER␣ (Sigma), according to the method described by Huang and colleagues (27). As a negative control, the serum pool was preincubated with 40 g/ml of bovine serum albumin (BSA; Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the antibody specificity, the serum pool obtained from patients with SLE who were positive for anti-ER␣ antibodies was diluted 1:100 in PBST and incubated overnight at room temperature in the presence of 40 g/ml of ER␣ (Sigma), according to the method described by Huang and colleagues (27). As a negative control, the serum pool was preincubated with 40 g/ml of bovine serum albumin (BSA; Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Apart from sensitizations to species-specific antigens, a number of polyvalent sensitizations have been found that probably are caused by cross-reactivity between homologous proteins and the polysaccharides common among different fungal species. Cross-reactivity between Malassezia and Candida albicans, molds, and even non-fungal species has been shown [18][19][20][21]. These data can explain why fungi-allergic patients show reactivity to several fungal species [22].…”
mentioning
confidence: 72%
“…Urticaria nicht bestätigen konnten oder eine Kreuzreaktivität zwischen Candida albicans und Pityrosporum ovale bzw. orbiculare sowie Saccharomyces cerevisiae zeigten [183,184,185,186]. Leider wurde in einer Studie von Middleton et al [134] …”
Section: Kann Eine Intestinale Candidabesiedelung Beim Menschen Zu Eiunclassified